Integration of Green Architecture and Renewable Energy in the Development of Sustainable Tourism Destinations (International Journal of Architecture and Urbanism, 2025)
In recent decades, the tourism sector has experienced rapid growth and become a key pillar of the global economy. However, this expansion has often been accompanied by significant environmental degradation, including increased carbon emissions, energy inefficiency, and ecosystem disruption. In response, the integration of green architecture and renewable energy has emerged as a vital strategy for promoting sustainable tourism development. This study aims to examine how these two approaches can be synergistically applied to create environmentally responsible, energy-efficient, and socially inclusive tourism destinations. Using a systematic literature review methodology, this research synthesizes findings from scholarly journals, international reports, and conference proceedings published between 2010 and 2025. The analysis focuses on three main dimensions: green architectural strategies in tourism design, the implementation of renewable energy systems such as solar PV and biomass, and the combined environmental, social, and economic impacts of their integration. Results indicate that green architecture contributes significantly to reducing energy consumption by up to 70%, while renewable energy enhances energy independence and lowers operational costs, especially in remote or off-grid destinations. Moreover, community participation in planning and operating these systems fosters local empowerment and sustainability awareness among tourists. The study also reveals existing gaps in the literature, including a lack of quantitative performance metrics and limited exploration of policy and institutional frameworks in developing countries. The findings affirm the relevance of sustainability theory and energy transition frameworks, highlighting the importance of cross-sectoral and interdisciplinary collaboration in implementing green solutions. This research contributes a comprehensive conceptual foundation for the design and planning of low-carbon tourism destinations and offers actionable recommendations for policymakers, urban planners, architects, and tourism stakeholders. Ultimately, integrating green architecture and renewable energy is not only feasible but essential in addressing climate challenges and ensuring a resilient and competitive future for global tourism